Contribution of foot joints in the energetics of human running - Deschamps, K.; Matricali, G.; Peters, H.; Eerdekens, M.; Wuite, S.; Leardini, A.; Staes, F. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
The foot seems to demonstrate considerable power absorption and generation characteristics during running. These have been mainly accounted to the mechanics of the ankle joint, however, evidence suggests that joint kinetics have been overestimated by single-segment foot models. The scope of the present study was to estimate the energetics of the ankle-, chopart-, lisfranc- and hallux joint during heel-strike running. Power absorption and generation occuring at different segments of the foot of seven asymptomatic adults was modelled using a four-segment kinetic foot model. Participants ran barefoot with an average running speed 3.5?m/s along a 10 meter walkway. The peak power generation of the ankle, chopart, lisfranc, and hallux joint reached respectively an average of 13.9, 4.12, 1.08 and 0.32 Watt/kg. The Lisfranc joint showed poor power absorption compared to the other three joints. It was further demonstrated that the Ankle and Chopart joints seem to have both receptive and propulsive characteristics. The behavior of the Lisfranc joint complied almost exclusively with propulsive characteristics. Finally, it can be concluded that the midfoot accounts for approximately 25% of the total power absorption occuring at the foot joints and not 50% as initially hypothesized.